REGENERASI SUMBER DAYA MANUSIA PERTANIAN DI KECAMATAN RUMBAI KOTA PEKANBARU BERBASIS DIGITAL HUMANITIES - Dery Alafghani Alim; Arifudin; Meki Herlon; Cepriadi; Roza Yulida; Zulhamid Ridho (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Regeneration of human resources in agriculture by younger farmers who are living with social media, called digital humanities, is one of the steps of its sustainability. This research aims to analyse regeneration of agricultural human resources model in Rumbai District of Pekanbaru City. The research used a survey method where 60 young farmers were taken as the samples. The data were analysed using SEM-PLS. The research results show that the use of social media provides easy access to information, increases knowledge and shares experiences related to the agricultural sector which is supported by the role of parents in forming perceptions and the interest of the younger generation in agriculture to work in the agriculture. The use of social media toward perception on agriculture and the use of social media on the attitudes of the younger generation towards the agriculture, are directly significant. On the other hand, a significant indirect influence is the use of social media on the interest of the younger generation in working in the agriculture through the mediator variable of the attitude of the younger generation towards the agriculture.